(untitled) (Interdisciplinary Studies Journal, 2024)
This essay aims to explain how the works Flicts and Autism: A Reality, written by Ziraldo, can engage with the reality of children with autism spectrum disorder. Another benefit would be that, with the right guidance, it would be possible to identify, even in childhood, how elements belonging to the reader’s reality influence the transmission of the message. Thus, addressing topics like autism in a deconstructed way is undoubtedly one of the most viable options for breaking stereotypes, in addition to raising awareness and explaining this issue to the reader, aiming at the construction of a consistent and, at the same time, provocative text. To do so, it is essential to consider the idea that literature allows a shift in our human experiences, and through this flow, we will attempt to perceive the world in a different way, experiencing it with a more critical and sensitive outlook.